Strategies to Reduce Catheter‐Related Bloodstream Infections in Pediatric Patients Receiving Home Parenteral Nutrition: The Efficacy of Taurolidine‐Citrate Prophylactic‐Locking. Issue 6 (31st January 2018) - Lambe, Cecile; Poisson, Catherine; Talbotec, Cecile; Goulet, Olivier
Abstract: Background: Catheter‐related bloodstream infections (CRBSIs) remain a major issue in patients who are receiving home parenteral nutrition (HPN). The aim of this interventional study was to assess the impact of a new strategy using taurolidine‐citrate (T‐C) prophylactic locks on the CRBSI rate in children with intestinal failure who are receiving HPN. Methods: The rate of CRBSIs was monitored every calendar year in a prospective cohort of 195 children with intestinal failure. T‐C locks were initiated from October 2011 in children with recurring CRBSIs (≥2 episodes per year). Results: In the whole cohort, the median annual CRBSI rate per 1000 catheter days decreased significantly from 2.07 in 2008 to 2010 to 1.23 in 2012 to 2014 ( P < .05). T‐C locks were used in 40 patients. No adverse events were reported. In taurolidine‐treated patients, the CRBSI rate per 1000 catheter days decreased from 4.16 to 0.25 ( P < .0001). The cumulative percentage of patients free of CRBSI at 18 months was 92% (95% confidence interval [CI]: 71–98) on T‐C lock vs 61% (95% CI: 49–72) in controls ( P = .01). In multivariate analysis, factors associated with CRBSI were immune deficiency (adjusted hazard ratio 3.49; 95% CI: 1.01–12.17) and the young age of the parents (adjusted hazard ratio 4.79, 95% CI: 2.16–10.62), whereas T‐C locks were protective (adjusted hazard ratio 0.22, 95% CI: 0.06–0.74). Conclusion: This study confirms the efficacy of T‐C catheter locks in decreasing the incidence of CRBSIs in children with intestinal failure who are receiving HPN.